2014
DOI: 10.1136/tobaccocontrol-2013-051246
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco on the web: surveillance and characterisation of online tobacco and e-cigarette advertising

Abstract: Online banner/video advertising is a tactic used mainly to advertise e-cigarettes and cigars rather than cigarettes, some with unproven claims about benefits to health. Given the reach and accessibility of online advertising to vulnerable populations such as youth and the potential for health claims to be misinterpreted, online advertisements need to be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 30 publications
(28 reference statements)
4
125
2
1
Order By: Relevance
“…For example, snus advertisements in the United States rarely feature harm reduction or smoking cessation. 20 Additionally, while a study in Sweden found that snus use is not associated with smoking initiation, 21 our previous research showed that snus use predicted subsequent combustible cigarette smoking in a cohort of US Midwest young adult nonsmokers. 22 Snus sold in the United States also seems to be different from that in Sweden.…”
Section: Trends In Awareness Use Of and Beliefs About Electronic CImentioning
confidence: 91%
See 1 more Smart Citation
“…For example, snus advertisements in the United States rarely feature harm reduction or smoking cessation. 20 Additionally, while a study in Sweden found that snus use is not associated with smoking initiation, 21 our previous research showed that snus use predicted subsequent combustible cigarette smoking in a cohort of US Midwest young adult nonsmokers. 22 Snus sold in the United States also seems to be different from that in Sweden.…”
Section: Trends In Awareness Use Of and Beliefs About Electronic CImentioning
confidence: 91%
“…36 E-cigarette advertisements also often feature messages related to harm reduction and/or smoking cessation. 4,20 In contrast, after spending US $62 million in 2010 to advertise snus in US magazines, tobacco companies spent only US $2-5 million per year between 2011 and 2014 to promote snus in magazines. 36 Additionally, in the United States, it was uncommon for snus advertisements to feature messages related to harm reduction and/or smoking cessation, but to feature flavors and price promotions.…”
mentioning
confidence: 99%
“…12 Furthermore, aggressive marketing campaigns for e-cigarettes are being conducted on prime-time television, on the Internet, at shopping malls, and at other venues readily accessible to adolescents. [13][14][15][16] Such considerations have led to concerns that e-cigarettes may lead to a renormalization of cigarette smoking, with this being a particular concern for younger populations, who show a high degree of awareness of e-cigarettes. 2,17 However, at present there is little empirical evidence on this issue.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Beliefs regarding e-cigarettes only emitting harmless water vapor led to the unrestricted usage of this device in public places (28)(29)(30). This erroneous belief may be due to the fact that e-cigarettes have been marketed with the emphasis that they do not release harmful smoke like conventional cigarettes do (2,31,32).…”
Section: Introductionmentioning
confidence: 99%